2022
DOI: 10.18393/ejss.1060314
|View full text |Cite
|
Sign up to set email alerts
|

Impact of NPK fertilization on hazelnut yield and soil chemical-microbiological properties of Hazelnut Orchards in Western Georgia

Abstract: In this study, the effects of ground and foliar applications of the NPK fertilizers in hazelnut orchards on the soil chemical and microbiological properties and hazelnut yield were investigated. The fertilization practicesses from ground were done two times using NPK (20:10:10 +trace elements) on March and May while the fertilization practices from leaf were done three times using NK (15:12 +trace elements) on May, June and July at six different hazelnut orchards located on Samegrelo, Guria and Adjara regions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
1
6
0
1
Order By: Relevance
“…However, in this case, as our studies have shown, it is desirable to leverage different characteristics of varieties for the development and generation of yields, which allows for a more flexible strategy (Kizilkaya et al, 2022;Valeriano et al, 2022). The generation of yield depends on many parameters of both the plant itself and its fruit, which has been repeatedly noted above.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…However, in this case, as our studies have shown, it is desirable to leverage different characteristics of varieties for the development and generation of yields, which allows for a more flexible strategy (Kizilkaya et al, 2022;Valeriano et al, 2022). The generation of yield depends on many parameters of both the plant itself and its fruit, which has been repeatedly noted above.…”
Section: Discussionmentioning
confidence: 66%
“…Since 2015, there have been significant shifts in climate resources in the region. The frost-free period has significantly increased, the vegetation of winter crops has become extended, the timing of the spring crops sowing has shifted, the period of adverse droughts has shifted, which rarely coincide with the critical stages in the development of agricultural plants (Banyal et al, 2021;Kizilkaya et al, 2022). In this regard, there was a question on expansion of the range of the crops,which are constantly grown in the region to increase profitability of economic activities in the North of Steppe of Ukraine, and to improve the diet of local population (Nazarenko et al, 2019a(Nazarenko et al, , 2021.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Al-Taey et al (2018) recorded that the application of fertilizers can improve plant growth and increase of N, P and K contents in tissue and their uptake. Gülser et al (2021) and Kızılkaya et al (2022) reported that fertilizers consist of N, P, K increase the uptake and utilization of nutrients by grain crops.…”
Section: Nutrient Contents In Seedsmentioning
confidence: 99%
“…Domestic research is mainly concerned with the problem of microclonal propagation of hazelnuts (Andrievsky et al 2019;Tarasenko et. al 2020;Kızılkaya et al 2022). A lot of work has been done in European countries regarding the microclonal propagation of hazelnuts and almonds, but in Ukraine, the scientific searches and industrial interest in these crops owing to increased demand for their fruits are developing rapidly.…”
Section: Introductionmentioning
confidence: 99%